Cancer outcome research – a European challenge Part II: Opportunities and priorities. Issue 12 (14th January 2022) - Kalager, Mette; Adami, Hans‐Olov; Dickman, Paul W.; Lagergren, Pernilla; Steindorf, Karen
Abstract : In Part I of our review of cancer outcome research, we analysed pros and cons of various measures relevant to quantifying the burden of cancer. Based on our recommendations in Part I, we now discuss in Part II opportunities and priorities in four areas of outcome research: primary prevention; early detection screening; treatment; and quality‐of‐life assessment. We recommend the establishment of an infrastructure that facilitates high‐quality research in these areas: (a) progress in primary prevention can be assessed most directly by monitoring cancer incidence although the interpretation of temporal trends is notoriously confounded by numerous factors that complicate causal inference. (b) preventive screening, with the aim to prevent advanced disease, appears to work well in in some tumours but not in others. It will require randomized control trials (RCTs) to quantify benefits and harms although conclusive studies are increasingly difficult to undertake. We therefore propose learning screening programmes (randomization at the time of rolling out population‐based programmes) as the most feasible approach. (c) New therapeutic interventions tailored to the individual patient often require assessment in RCTs with rather complex and dynamic structure, making their design and analyses increasingly challenging but also more suited to be executed as academic, PI‐initiated trials. (d) We next discuss assessment of quality‐of‐life aspects. Quality of life is a neglected component in outcome research with an urgent need for development, validation and standardization. We finally recommend four initiatives that would pave the way for a valid and informative assessment of the goals for improved cancer control in Europe as defined by the European Academy of Cancer Sciences. Abstract : This policy paper outlines the urgent needs and opportunities in Europe to undertake cutting‐edge cancer outcome research. Recommendations are provided for the most urgent measures in the four domains: cancer prevention, screening, treatment and quality of life. We propose an infrastructure and opportunities that can facilitate high‐quality outcome research, including learning screening programmes with dynamic randomised trials (RCTs).